2022
DOI: 10.3390/foods11030270
|View full text |Cite
|
Sign up to set email alerts
|

Italian Tomato Cultivars under Drought Stress Show Different Content of Bioactives in Pulp and Peel of Fruits

Abstract: Background: This study aims to evaluate the performance, in terms of accumulation of antioxidant compounds in fruits, of nine local and three commercial Italian tomato cultivars subjected to drought stress. The same local cultivars had been previously studied at morpho-physiological level. Methods: The present manuscript analyzes drought stress as a tool to increase the amount of secondary metabolites that can enhance fruit quality. Nutraceutical characterization of the fruits was performed by analyzing the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…It should also be considered that different tomato cultivars exhibit different biochemical responses in relation to their specific genetic background. In previous works we have already observed that locally adapted Tuscan tomato cultivars exhibit different responses in physiological terms [53,54], as well as in the content of polyphenols and antioxidants at the fruit level [55].…”
Section: Introductionmentioning
confidence: 93%
“…It should also be considered that different tomato cultivars exhibit different biochemical responses in relation to their specific genetic background. In previous works we have already observed that locally adapted Tuscan tomato cultivars exhibit different responses in physiological terms [53,54], as well as in the content of polyphenols and antioxidants at the fruit level [55].…”
Section: Introductionmentioning
confidence: 93%
“…192 In response to drought stress conditions, aroma enrichment was noticed in tomatoes and strawberries. 194 Water deficit conditions have improved the content of aromatic compounds, especially C13-norisoprenoids, which impart fruity character to berries and wine. 195 In apples also, root zone drying has shown positive effects on the accumulation of aroma compounds.…”
Section: Up-/downregulation Of Phenylpropanoid and Flavonoid Pathways...mentioning
confidence: 99%
“…The AO treatment had the lowest ASA content, as the application of AO alone reduced the ASA content compared to the control (Figure 6B). Conti et al (2022), in a study they conducted with 12 different tomato cultivars exposed to drought stress, stated that drought stress caused an increase in the ASA content of some cultivars while a decrease in some cultivars. The fact that ASA content was found to be the highest in AO+D application in the current study can be considered as one of the important signs that AO has positive effects on the antioxidant system of maize seedlings under drought stress.…”
Section: Proline Contentmentioning
confidence: 99%